Is Earnings Nonresponse Ignorable? - Bollinger, Christopher R.; Hirsch, Barry T. (The Review of Economics and Statistics, 2013)
Earnings nonresponse in the Current Population Survey is roughly 30% in the monthly surveys and 20% in the March survey. If nonresponse is ignorable, unbiased estimates can be achieved by omitting nonrespondents. Little is known about whether CPS nonresponse is ignorable. Using sample frame measures to identify selection, we find clear-cut evidence among men but limited evidence among women for negative selection into response. Wage equation slope coefficients are affected little by selection, but because of intercept shifts, wages for men and, to a lesser extent, women are understated, as are gender gaps. Selection is least severe among household heads. © 2013 The President and Fellows of Harvard College and the Massachusetts Institute of Technology.